Effects of Laminaria Japonica Polysaccharides on the Survival of Non-Small-Cell Lung Cancer A549 Cells - Mengxing Yao; XiaoJun Qian; Houying Qin (International Journal of Polymer Science)
Objective. To investigate the effect of Laminaria japonica polysaccharides (LJP) on the survival of non-small-cell lung cancer (NSCLC) A549 cells and its mechanism. Methods. In vitro: the cells were randomly divided into control group, LJP (5 mg/ml) group, LJP (10 mg/ml) group, and LJP (20 mg/ml) group. After corresponding treatment, the survival rate and the expression of proteins related to proliferation, apoptosis, epithelial-mesenchymal transition (EMT), and signaling pathway were detected by CCK8 assay and Western blot, respectively. In vivo: a xenograft model was established to detect the tumor volume and mass and the expression of the above pathway proteins. Results. Compared with the control group, LJP decreased the survival rate of A549 cells (P<0.05), inhibited the protein expression of Ki67 and PCNA (P<0.05), downregulated the expression of Bcl-2 while upregulated the expression of Bax, cl-caspase-3, and cl-caspase-9 (P<0.05), upregulated the expression of E-cadherin, downregulated the expression of vascular endothelial growth factor (VEGF) and N-cadherin (P<0.05), and downregulated β-catenin, transcription factor-4 (TCF4), and c-Myc protein expression levels (P<0.05). In vivo: LJP decreased the volume and mass of the xenograft tumors and downregulated β-catenin, TCF4, and c-Myc protein expression levels compared with the control group (P<0.05). Conclusion. LJP can inhibit the survival of non-small-cell lung cancer A549 cells in vitro, and its mechanism is related to the inhibition of activation of β-catenin/TCF4 pathway activation.